The Christian New Culture Movement and Xie Songgao’s Concept of Citizenship - ZHAO, Xiaohui (Journal of Research for Christianity in China (JRCC), 2025)
The May Fourth Movement’s new intellectual currents prompted religious figures to reexamine Christianity’s historical role and its value and significance for modern Chinese society. Amidst the prevailing national consciousness focused on survival and rejuvenation, a group of Christian intellectuals embraced dual identities as both “Christians” and “Chinese” to shoulder the responsibility of saving the nation and reviving the people, sparking a Christian New Culture Movement. Xie Songgao (1895-1974) stood as one of its most prominent representatives. Employing both “invisible enlightenment” and “visible enlightenment,” he undertook extensive efforts to cultivate the ideal citizen he envisioned, striving to modernize humanity and thereby propel China toward genuine modernization. This paper primarily examines Xie Songgao’s conception of citizenship, highlighting how his educational enlightenment efforts—driven by the May Fourth intellectual currents and the Christian New Culture Movement—objectively advanced China’s modernization process. The principles he contributed to building China’s civil society retain significant value to this day.